Skip to content
New issue

Have a question about this project? Sign up for a free GitHub account to open an issue and contact its maintainers and the community.

By clicking “Sign up for GitHub”, you agree to our terms of service and privacy statement. We’ll occasionally send you account related emails.

Already on GitHub? Sign in to your account

binomial lemmas for *-commuting elements in a Semiring #1927

Merged
merged 8 commits into from
Feb 28, 2023
Merged
Show file tree
Hide file tree
Changes from all commits
Commits
File filter

Filter by extension

Filter by extension

Conversations
Failed to load comments.
Loading
Jump to
Jump to file
Failed to load files.
Loading
Diff view
Diff view
22 changes: 22 additions & 0 deletions CHANGELOG.md
Original file line number Diff line number Diff line change
Expand Up @@ -1685,6 +1685,15 @@ Other minor changes
middleSemimedial : ∀ x y z → (x ∙ y) ∙ (z ∙ x) ≈ (x ∙ z) ∙ (y ∙ x)
semimedial : Semimedial _∙_
```
* Added new proof to `Algebra.Properties.Monoid.Mult`:
```agda
×-congˡ : ∀ {x} → (_× x) Preserves _≡_ ⟶ _≈_
```

* Added new proof to `Algebra.Properties.Monoid.Sum`:
```agda
sum-init-last : ∀ {n} (t : Vector _ (suc n)) → sum t ≈ sum (init t) + last t
```

* Added new proofs to `Algebra.Properties.Semigroup`:
```agda
Expand All @@ -1694,6 +1703,19 @@ Other minor changes
flexible : Flexible _∙_
```

* Added new proofs to `Algebra.Properties.Semiring.Exp`:
```agda
^-congʳ : (x ^_) Preserves _≡_ ⟶ _≈_
y*x^m*y^n≈x^m*y^[n+1] : (x * y ≈ y * x) → y * (x ^ m * y ^ n) ≈ x ^ m * y ^ suc n
```

* Added new proofs to `Algebra.Properties.Semiring.Mult`:
```agda
1×-identityʳ : 1 × x ≈ x
×-comm-* : x * (n × y) ≈ n × (x * y)
×-assoc-* : (n × x) * y ≈ n × (x * y)
```

* Added new proofs to `Algebra.Properties.Ring`:
```agda
-1*x≈-x : ∀ x → - 1# * x ≈ - x
Expand Down
3 changes: 3 additions & 0 deletions src/Algebra/Properties/Monoid/Mult.agda
Original file line number Diff line number Diff line change
Expand Up @@ -46,6 +46,9 @@ open import Algebra.Definitions.RawMonoid rawMonoid public
×-cong : _×_ Preserves₂ _≡_ ⟶ _≈_ ⟶ _≈_
×-cong {n} P.refl x≈x′ = ×-congʳ n x≈x′

×-congˡ : ∀ {x} → (_× x) Preserves _≡_ ⟶ _≈_
×-congˡ m≡n = ×-cong m≡n refl

-- _×_ is homomorphic with respect to _ℕ+_/_+_.

×-homo-+ : ∀ x m n → (m ℕ.+ n) × x ≈ m × x + n × x
Expand Down
18 changes: 18 additions & 0 deletions src/Algebra/Properties/Monoid/Sum.agda
Original file line number Diff line number Diff line change
Expand Up @@ -31,6 +31,7 @@ open Monoid M
open import Data.Vec.Functional.Relation.Binary.Equality.Setoid setoid
open import Algebra.Properties.Monoid.Mult M
open import Algebra.Definitions _≈_
open import Relation.Binary.Reasoning.Setoid setoid

------------------------------------------------------------------------
-- Definition
Expand Down Expand Up @@ -70,3 +71,20 @@ sum-replicate-idem idem n = trans (sum-replicate n) (×-idem idem n)
sum-replicate-zero : ∀ n → sum {n} (replicate 0#) ≈ 0#
sum-replicate-zero zero = refl
sum-replicate-zero (suc n) = sum-replicate-idem (+-identityˡ 0#) (suc n)

-- When summing over a `Vector`, we can pull out last element

sum-init-last : ∀ {n} (t : Vector Carrier (suc n)) → sum t ≈ sum (init t) + last t
sum-init-last {zero} t = begin
t₀ + 0# ≈⟨ +-identityʳ t₀ ⟩
t₀ ≈˘⟨ +-identityˡ t₀ ⟩
0# + t₀ ∎ where t₀ = t zero
sum-init-last {suc n} t = begin
t₀ + ∑t ≈⟨ +-congˡ (sum-init-last (tail t)) ⟩
t₀ + (∑t′ + tₗ) ≈˘⟨ +-assoc _ _ _ ⟩
(t₀ + ∑t′) + tₗ ∎
where
t₀ = head t
tₗ = last t
∑t = sum (tail t)
∑t′ = sum (tail (init t))
31 changes: 30 additions & 1 deletion src/Algebra/Properties/Semiring/Exp.agda
Original file line number Diff line number Diff line change
Expand Up @@ -15,7 +15,7 @@ import Data.Nat.Properties as ℕ
module Algebra.Properties.Semiring.Exp
{a ℓ} (S : Semiring a ℓ) where

open Semiring S renaming (zero to *-zero)
open Semiring S
open import Relation.Binary.Reasoning.Setoid setoid
import Algebra.Properties.Monoid.Mult *-monoid as Mult

Expand All @@ -34,10 +34,39 @@ open import Algebra.Definitions.RawSemiring rawSemiring public
^-cong : _^_ Preserves₂ _≈_ ⟶ _≡_ ⟶ _≈_
^-cong x≈y u≡v = Mult.×-cong u≡v x≈y

^-congʳ : ∀ x → (x ^_) Preserves _≡_ ⟶ _≈_
^-congʳ x = Mult.×-congˡ

-- xᵐ⁺ⁿ ≈ xᵐxⁿ
^-homo-* : ∀ x m n → x ^ (m ℕ.+ n) ≈ (x ^ m) * (x ^ n)
^-homo-* = Mult.×-homo-+

-- (xᵐ)ⁿ≈xᵐ*ⁿ
^-assocʳ : ∀ x m n → (x ^ m) ^ n ≈ x ^ (m ℕ.* n)
^-assocʳ x m n rewrite ℕ.*-comm m n = Mult.×-assocˡ x n m

------------------------------------------------------------------------
-- A lemma using commutativity, needed for the Binomial Theorem

y*x^m*y^n≈x^m*y^[n+1] : ∀ {x} {y} (x*y≈y*x : x * y ≈ y * x) →
∀ m n → y * (x ^ m * y ^ n) ≈ x ^ m * y ^ suc n
y*x^m*y^n≈x^m*y^[n+1] {x} {y} x*y≈y*x = helper
where
helper : ∀ m n → y * (x ^ m * y ^ n) ≈ x ^ m * y ^ suc n
helper zero n = begin
y * (x ^ ℕ.zero * y ^ n) ≡⟨⟩
y * (1# * y ^ n) ≈⟨ *-congˡ (*-identityˡ (y ^ n)) ⟩
y * (y ^ n) ≡⟨⟩
y ^ (suc n) ≈˘⟨ *-identityˡ (y ^ suc n) ⟩
1# * y ^ (suc n) ≡⟨⟩
x ^ ℕ.zero * y ^ (suc n) ∎
helper (suc m) n = begin
y * (x ^ suc m * y ^ n) ≡⟨⟩
y * ((x * x ^ m) * y ^ n) ≈⟨ *-congˡ (*-assoc x (x ^ m) (y ^ n)) ⟩
y * (x * (x ^ m * y ^ n)) ≈˘⟨ *-assoc y x (x ^ m * y ^ n) ⟩
y * x * (x ^ m * y ^ n) ≈˘⟨ *-congʳ x*y≈y*x ⟩
x * y * (x ^ m * y ^ n) ≈⟨ *-assoc x y _ ⟩
x * (y * (x ^ m * y ^ n)) ≈⟨ *-congˡ (helper m n) ⟩
x * (x ^ m * y ^ suc n) ≈˘⟨ *-assoc x (x ^ m) (y ^ suc n) ⟩
(x * x ^ m) * y ^ suc n ≡⟨⟩
x ^ suc m * y ^ suc n ∎
27 changes: 27 additions & 0 deletions src/Algebra/Properties/Semiring/Mult.agda
Original file line number Diff line number Diff line change
Expand Up @@ -33,3 +33,30 @@ open import Algebra.Properties.Monoid.Mult +-monoid public
n × 1# + (m × 1#) * (n × 1#) ≈˘⟨ +-congʳ (*-identityˡ _) ⟩
1# * (n × 1#) + (m × 1#) * (n × 1#) ≈˘⟨ distribʳ (n × 1#) 1# (m × 1#) ⟩
(1# + m × 1#) * (n × 1#) ∎

-- (1 ×_) is the identity

1×-identityʳ : ∀ x → 1 × x ≈ x
1×-identityʳ = +-identityʳ

-- (n ×_) commutes with _*_

×-comm-* : ∀ n x y → x * (n × y) ≈ n × (x * y)
×-comm-* zero x y = zeroʳ x
×-comm-* (suc n) x y = begin
x * (suc n × y) ≡⟨⟩
x * (y + n × y) ≈⟨ distribˡ _ _ _ ⟩
x * y + x * (n × y) ≈⟨ +-congˡ (×-comm-* n _ _) ⟩
x * y + n × (x * y) ≡⟨⟩
suc n × (x * y) ∎

-- (n ×_) associates with _*_

×-assoc-* : ∀ n x y → (n × x) * y ≈ n × (x * y)
×-assoc-* zero x y = zeroˡ y
×-assoc-* (suc n) x y = begin
(suc n × x) * y ≡⟨⟩
(x + n × x) * y ≈⟨ distribʳ _ _ _ ⟩
x * y + (n × x) * y ≈⟨ +-congˡ (×-assoc-* n _ _) ⟩
x * y + n × (x * y) ≡⟨⟩
suc n × (x * y) ∎